ANALISA INDEPENDENSI PENILAIAN JAMINAN UTANG KREDIT BANK - Dian Ayu Rahmadani; I Wayan Priyana Agus Sudharma; Putu Ayu Meidha Suwandewi (Nusantara Hasana Journal, 2022)
The difference in the credit guarantee assessment procedure by the bank’s internal appraiser and the independent appraiser can be seen in the scope of the assignment where in this case the bank is the user of the report, while the KJPP is the party assigned the task of conducting the assessment. The bank’s internal appraiser uses the same assessment procedure but still pays attention to the existence of acceptable credit risk, therefore sometimes banks use the lowest value related to credit applications. Meanwhile, to perform the analysis and basis for object valuation, the two appraisers use the same procedure using a market approach and a cost approach based on the applicable regulations, namely the Indonesian Appraisal Standard (SPI) and the Indonesian Appraisal Code of Ethics (KEPI).